Using the miscue reading inventory - Tatlonghari, Melchor A. (2002)
Research on reading process has consistently emphasized the active role of teacher as they use print clues to "conduct" a model of the text's meaning. it suggests that at all levels of sophistication, readers use available resources to make sense of the text.
Keywords: Reading comprehension -- Research; Miscue analysis; Reading achievement